"FAST-TRACK" to Organ and Tissue Donation Training: An Alternative to Out-Of-Time Intensive Care and Emergency Health Care Professionals. (August 2017) - Sarlo, Rodrigo; Barros, Onofre; de Almeida, Ana Carolina; Vascouto, Gisele; Paura, Priscila; da Costa, Ana Claudia; Galdiano, Leandro; Rocha, Eduardo
Abstract : Introduction: Throughout the world, intensive care (ICU) and emergency professionals face an extremely exhaustive work shift. Finding spare time for education and training in different areas, including organ and tissue donation, presents as an additional difficult task. We have previously reported the beneficial effects of training ICU professionals on increasing the number of organ and tissue donors in Rio de Janeiro, Brazil. Objectives: To further increase the number of ICU and emergency professionals involved with the donation process, considering the lack of time available, we have created a short-duration training program to be applied during working hours, named FAST-TRACK for organ and tissue donation. Methods: Trained OPO professionals visited ICU and Emergency Departments of 42 hospitals, performing a 6 questions pre-evaluation test, followed by a 15 min oral presentation and a post-test. Tests were performed at the ICU or emergency wards, following consent from the administration offices. Questions were focused on major areas linked to the donation process: Brain Death, Mechanical Ventilation, Family Communication, Logistics, Legislation and Donor Management. Pre and post tests results were compared and shared with health care professionals. Improvements in the donation process were presented as percent increase in correct responses (>%). Results: 571 ICU and/or emergency professionals participated in the FAST-TRACK program with only one refusal to take the tests. Comparing pre and post tests, a significant increase in correct responses was observed, in the following areas (picture attached). Combining the results, we noticed improvement in all topics. Discussion: Considering the limitations of the program, fast track training on organ and tissue donation for ICU and emergency professionals resulted as a good alternative to formal, long-lasting training. Considering the usual lack-of-time observed in most hospitals and the short time consumed, the program was well-accepted and showed positive results. Adjusts to the questionnaire and methods according to different areas in the world may be necessary. Figure. No caption available.